2009
DOI: 10.1159/000218088
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cold Dialysate Regeneration System for Home Hemodialysis

Abstract: Background/Aims: Because longer and/or more frequent dialysis has potential clinical benefits, home hemodialysis (HHD) systems should provide flexible renal replacement therapies. We propose a new cold dialysate regeneration system that requires 10 l per treatment for HHD. Methods: We designed a dialysate regeneration system using cold dialysate and 2 activated carbon columns alternatively switched between adsorption and desorption. Urea adsorption ratios were compared in three different conditions; cold dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Previously, we found that the urea adsorption ratio (UAR) of the CDRS was independent of the initial urea concentration but varied with the dialysate flow rate and perfusion time [15] . In that study, we obtained the time-varying UAR of the CDRS at a dialysate flow rate of 300 ml/min experimentally.…”
Section: Adsorption Model Of the Cdrsmentioning
confidence: 98%
See 4 more Smart Citations
“…Previously, we found that the urea adsorption ratio (UAR) of the CDRS was independent of the initial urea concentration but varied with the dialysate flow rate and perfusion time [15] . In that study, we obtained the time-varying UAR of the CDRS at a dialysate flow rate of 300 ml/min experimentally.…”
Section: Adsorption Model Of the Cdrsmentioning
confidence: 98%
“…During HD treatment, one column adsorbs toxins, and the other desorbs the toxins in order to maintain the adsorptive efficacy of the CDRS. A more detailed description of the CDRS was presented in our previous paper [15] .…”
Section: Description Of the Cdrsmentioning
confidence: 99%
See 3 more Smart Citations